2014
DOI: 10.1021/ja411138s
|View full text |Cite
|
Sign up to set email alerts
|

Superselective Targeting Using Multivalent Polymers

Abstract: Despite their importance for material and life sciences, multivalent interactions between polymers and surfaces remain poorly understood. Combining recent achievements of synthetic chemistry and surface characterization, we have developed a well-defined and highly specific model system based on host/guest interactions. We use this model to study the binding of hyaluronic acid functionalized with host molecules to tunable surfaces displaying different densities of guest molecules. Remarkably, we find that the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
158
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 98 publications
(178 citation statements)
references
References 26 publications
(55 reference statements)
13
158
0
Order By: Relevance
“…This aspect of multivalency has recently been described by Frenkel and co-workers and could explain a faster than linear increase of cellbound nanogels with the density of available mannose ligands. [59][60][61] Such trend appears in our present work but requires more in depth investigation.…”
supporting
confidence: 75%
“…This aspect of multivalency has recently been described by Frenkel and co-workers and could explain a faster than linear increase of cellbound nanogels with the density of available mannose ligands. [59][60][61] Such trend appears in our present work but requires more in depth investigation.…”
supporting
confidence: 75%
“…The box size in the vertical z direction is sufficiently large to ensure that none of the particles ever interacts with the hard ceiling or the floor. The simulations started with the particle center of mass at height R + σ above the membrane and were run for 6·10 6 cycles, where in each cycle on average one translational/rotational move per every bead and particle is attempted.…”
Section: Methodsmentioning
confidence: 99%
“…Such selectivity can be achieved by exploiting multivalency. A series of recent experimental and theoretical papers have shown that multivalent carriers (nanoparticles or polymers) can distinguish target surfaces (cells) on the basis of their receptor concentration, rather than just on the basis of the presence of a suitable receptor (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…For example, investigations of multivalent binding of polymers to surfaces lacked specificity [e.g., due to polymer-polymer interactions (14,15)] and suffered from poor experimental control over the density of ligands/ receptors on polymer (10, 11) and surface (14,15). With a welldefined model system based on host-guest interactions, we recently overcame these limitations and provided, to our knowledge, the first quantitative experimental demonstration of superselective binding of multivalent polymers to surfaces (16).…”
mentioning
confidence: 99%